The Creation Of Newspaper Corpora (Texas Journal of Philology, Culture and History, 2024)
Newspaper corpora are invaluable tools for studying contemporary language, media discourse, and sociopolitical trends. This article explores the methods used to create corpora from newspaper publications, addressing challenges such as data volume, genre variation, and temporal shifts. It also highlights key contributions by researchers like Tony McEnery, Ramesh Krishnamurthy, and Paul Baker, who have developed influential newspaper corpora. Through these corpora, linguists and social scientists gain insights into journalistic language, media framing, and linguistic change. This article outlines best practices for building newspaper corpora and discusses their significance for both linguistic and computational research.